Cationic Channel TRPV2 Overexpression Promotes Resistance to Cisplatin-Induced Apoptosis in Gastric Cancer Cells - Laurino, Simona; Mazzone, Pellegrino; Ruggieri, Vitalba; Zoppoli, Pietro; Calice, Giovanni; Lapenta, Antonella; Ciuffi, Mario; Ignomirelli, Orazio; Vita, Giulia; Sgambato, Alessandro; Russi, Sabino; Falco, Geppino (Frontiers in Pharmacology, 2021)
Gastric cancer (GC) is characterized by poor efficacy and modest clinical impact of current therapies, in which apoptosis evasion is relevant. Intracellular calcium homeostasis dysregulation is associated with apoptosis escaping and aberrant expression of calcium regulator genes could promote GC drug resistance. Since we previously found a prognostic value for TRPV2 calcium channel expression in GC, we aimed to characterize the role of TRPV2 in cisplatin resistance. Using the TCGA-STAD dataset, we performed a differential gene expression analysis between GC samples in upper and lower tertiles of TRPV2 expression, then trough a gene set analysis we highlighted the enriched ontology and canonical pathways. We used qRT-PCR to assess TRPV2 expression in three GC cell lines and flow cytometry to evaluate cisplatin-induced cell death rates. Calcium Green-1-AM assay was used to estimate differences in intracellular Ca2+ concentrations after inhibition of TRPV2. We engineered AGS cell line to overexpress TRPV2 and used confocal microscopy to quantify its overexpression and localization, and flow cytometry to evaluate their sensitivity to cisplatin. Consistent with our hypothesis, among enriched gene sets, we found a significant number of those involved in the regulation of apoptosis. Subsequently, we found an inverse correlation between TRPV2 expression and sensitivity to cisplatin in GC cell lines. Moreover, we demonstrated that inhibition of TRPV2 activity by Tranilast blocks the efflux of Ca2+ ions and, in combination with cisplatin, induced a significant increase of apoptotic cells (p = 0.004). We also demonstrated that TRPV2 exogenous expression confers a drug-resistant phenotype and that Tranilast is able to revert this phenotype, restoring cisplatin sensitivity. Our findings consistently suggested that TRPV2 could be a potential target for overcoming cisplatin resistance by promoting apoptosis. Notably, our data are a prerequisite for the potential reposition of Tranilast to the treatment of GC patients and anticipate the in vivo evaluation.